Risk Management in the Seafood Frozen Food Supply Chain Using the House of Risk Method - M. Alex Fatchurrochim; Evi Yuliawati; Clora Widya Brilliana (JTI: Jurnal Teknik Industri, 2025)
The frozen seafood supply chain, especially in emerging markets like Indonesia, is prone to various operational risks, including raw material degradation, inconsistent storage temperatures, and human error. PT Winaros Kawula Bahari, a shrimp processing company expanding into the Japanese market, faces these critical risks that threaten efficiency and product quality. This study aims to identify, analyze, and prioritize supply chain risks in the frozen seafood industry to support risk-based decision-making. This research employs the House of Risk (HoR) method, a proactive supply chain risk management approach combining Failure Modes and Effects Analysis (FMEA) with the House of Quality (HoQ). A mixed-methods approach was used, involving three domain experts (procurement, production, and logistics) to assess the severity and occurrence of risks. Risk events and agents were identified and evaluated using Aggregate Risk Potential (ARP), followed by the prioritization of mitigation actions in HoR Phase 2. The analysis identified 9 risk events and 22 risk agents. Based on ARP values, two dominant risk agents were identified: labor negligence and insufficient shrimp temperature during handling, which together accounted for over 25% of total ARP. Recommended mitigation strategies include enhanced supervision, occupational health and safety (OHS) training, supplier evaluation, and continuous quality audits. This study provides practical guidance for small and medium seafood enterprises in implementing data-driven supply chain risk management strategies. It sets the groundwork for integrating dynamic or fuzzy HoR methods in future research. Keywords: Frozen Food, House of Risk, Supply Chain Management, Risk, SCOR